Self-assembled nickel cubanes as oxygen evolution catalysts. Issue 69 (9th August 2021) - García-Álvarez, Ana C.; Gamboa-Ramírez, Stefani; Martínez-Otero, Diego; Orio, Maylis; Castillo, Ivan
Abstract : Ni4 O4 cubanes [(μ3 -L 1 O )NiCl(MeOH)]4 (1 ) and [(μ3 -L 2 O )NiCl(H2 O)]4 (2 ) (L 1 OH = 1- H -2-benzimidazolylmethanol, L 2 OH = 1-methyl-2-benzimidazolylmethanol) self-assemble, providing easy access to oxygen evolution electrocatalysts. Abstract : Ni4 O4 cubanes [(μ3 -L 1 O )NiCl(MeOH)]4 (1 ) and [(μ3 -L 2 O )NiCl(H2 O)]4 (2 ) (L 1 OH = 1- H -2-benzimidazolylmethanol, L 2 OH = 1-methyl-2-benzimidazolylmethanol) self-assemble from commercially available 1- H - and 1-methyl-2-benzimidazolylmethanol and NiCl2 ·6H2 O in high yields under mild conditions. Both complexes were characterised spectroscopically and by X-ray crystallography. The cubanes oxidise water electrocatalytically to dioxygen at neutral pH in aqueous potassium phosphate buffer solutions.